Polymer/Graphene oxide nanocomposite thin film for NO2 sensor - Sahu, Praveen Kumar; Pandey, Rajiv K.; Dwivedi, R.; Mishra, V. N.; Prakash, R. (Nature Research, 2020)
The higher operating temperature of metal oxide and air instability of organic based NO2 sensor causes extremely urgent for development of a reliable low cost sensor to detect NO2 at room temperature. Therefore, we present a fabrication of large area Polymer/GO nano hybrid thin flm for polymer thin flm transistors (PTFTs) based NO2 sensors assisted via facile method named ‘spreadingsolidifying (SS) method’, grown over air/liquid interface and successive investigation of efect of NO2 on flm via several characterizations. The PTFTs sensor has demonstrated swift and high response towards low concentration of NO2 gas with air stability and provided real time non-invasive type NO2 sensor. Herein, we are reporting the nanohybrid PBTTT/GO composite based PTFT sensor with good repeatability and sensor response for low concentration NO2. The thin flm grown via SS technique has reported very good adsorption/desorption of target analyte having response/recovery time of 75s/523s for 10 ppm concentration of NO2 gas. It has been observed that % change in drain current (sensor response) saturated with increasing concentration of NO2. The transient analysis demonstrates the fast sensor response and recovery time. Furthermore, in order to understand the insight of high performance of sensor, efect of NO2 on nanohybrid flm and sensing mechanism, an in situ investigations was conducted via multiple technique viz. spectral, electronic, structural, and morphological characterization. Finally, the performance of sensor and the site of adsorption of NO2 at polymer chains were argued using schematic diagram. This work shows the simple fabrication process for mass production, low cost and room temperature operated gas sensors for monitoring the real-time environment conditions and gives an insight about the sensing mechanism adsorption site of NO2.
An in situ investigation of electronic, morphological, structural, and spectroscopic properties
Keywords: Polymer; Graphene oxide; Thin flm